Implementation of integral control state feedback controller on prasmatic control of universal strech and bending machine (USBM) simplified model - Nik Mohd. Farhan, Abd Wahab (2008)
This project presents the ability of pneumatic cylinder for controlling the prasmatic movement using implementations of Programmable Logic Controller (PLC). The design and modeling for pneumatic cylinder position control is using State-Space technique. A mathematical model of the system can be derived and verified by using SIMULINK/MATLAB. It is important to verify simulation result through experiment and compare it with expected result. As we know, many functions can be implemented using Programmable Logic Controller (PLC). PLC also can integrate with pneumatic valve in order to design a controller. The aim of this project is to implement integral Control State Feedback controller algorithm (controlling prasmatic movement of pneumatic valve) by using PLC. The controller algorithm that has been chosen is Integral Control State Feedback Control of Universal Stretch and Bending Machine (USBM) Simplified Model. This system using two input and one output which are set point and feedback sensor as their input and the movement of cylinder pneumatic is their output.